2012
DOI: 10.1021/jf300483v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Esterified Lactoferrin and Lactoferrin on Control of Postharvest Blue Mold of Apple Fruit and Their Possible Mechanisms of Action

Abstract: The effects of esterified lactoferrin (ELF) and lactoferrin (LF) on blue mold caused by Penicillium expansum in apple fruit stored at 25 °C were investigated. Both ELF and LF provided an effective control and strongly inhibited spore germination and germ tube elongation of P. expansum in vitro. Assessment by propidium iodide staining combined with fluorescent microscopy revealed that the plasma membrane of P. expansum spores was damaged more seriously by ELF than by LF treatment, and the leakage of protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The inhibitory effect of YC1 on spore germination of P. expansum was assessed in potato dextrose broth (PDB) using the method described by Wang et al (2012). Aliquots (100 ll) of a condial suspension of P. expansum (1 9 10 7 spores/ml) were transferred to 15 ml glass tubes containing 5.0 ml PDB.…”
Section: Inhibition Of Spore Germinationmentioning
confidence: 99%
“…The inhibitory effect of YC1 on spore germination of P. expansum was assessed in potato dextrose broth (PDB) using the method described by Wang et al (2012). Aliquots (100 ll) of a condial suspension of P. expansum (1 9 10 7 spores/ml) were transferred to 15 ml glass tubes containing 5.0 ml PDB.…”
Section: Inhibition Of Spore Germinationmentioning
confidence: 99%
“…As important pathogenesis-related (PR) proteins, chitinase and β -1,3-glucanase are able to degrade fungal cell wall composed of chitin and β -glucan, which exhibit antifungal properties including delaying growth of hyphae and spore germination as well as decreasing the incidence of pathogen infection [47]. Similarly, elicitor or pathogen also could induce a significant increase in chitinase and β -1,3-glucanase activities in plants [13, 26, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…The amount of cinnamic acid produced was taken as a measure of enzyme activity using an increase in the absorbance of 0.01 at 290 nm. POD activity was determined using guaiacol as substrate [27]. The reaction mixture containing 0.5 mL supernatant preparation and 1.5 mL guaiacol (10 mM, in 100 mM sodium phosphate buffer, pH 6.8) was incubated for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The positive charge surface of a protein was then able to act on the negatively charged cell membrane in order to play a role in inhibiting the growth of bacteria [ 9 , 12 ]. Wang et al [ 13 ] found that lactoferrin, after esterification, carried positive charges and had a direct fungitoxic property against the pathogens of blue mold in apple fruit. Sitohy et al [ 9 ] found that esterified legume proteins had a good inhibitory effect on Gram-positive and Gram-negative bacteria due to the presence of static electricity.…”
Section: Introductionmentioning
confidence: 99%